2020
DOI: 10.2196/18331
|View full text |Cite
|
Sign up to set email alerts
|

Blood Uric Acid Prediction With Machine Learning: Model Development and Performance Comparison

Abstract: Background Uric acid is associated with noncommunicable diseases such as cardiovascular diseases, chronic kidney disease, coronary artery disease, stroke, diabetes, metabolic syndrome, vascular dementia, and hypertension. Therefore, uric acid is considered to be a risk factor for the development of noncommunicable diseases. Most studies on uric acid have been performed in developed countries, and the application of machine-learning approaches in uric acid prediction in developing countries is rare.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Considering the limited number of studies conducted by using ML in prediction models in dentistry, it is difficult to compare our study with the existing studies. Although most ML-based prediction models used in the field of medicine demonstrated improved performance compared to traditional statistical methods [43][44][45], not all showed a higher performance than regression models developed in these studies. For example, Sampa et al [43] developed a blood uric acid prediction model using multiple ML algorithms and reported that the boosted decision tree model showed improved performance compared to the traditional linear regression model.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Considering the limited number of studies conducted by using ML in prediction models in dentistry, it is difficult to compare our study with the existing studies. Although most ML-based prediction models used in the field of medicine demonstrated improved performance compared to traditional statistical methods [43][44][45], not all showed a higher performance than regression models developed in these studies. For example, Sampa et al [43] developed a blood uric acid prediction model using multiple ML algorithms and reported that the boosted decision tree model showed improved performance compared to the traditional linear regression model.…”
Section: Discussionmentioning
confidence: 73%
“…Although most ML-based prediction models used in the field of medicine demonstrated improved performance compared to traditional statistical methods [43][44][45], not all showed a higher performance than regression models developed in these studies. For example, Sampa et al [43] developed a blood uric acid prediction model using multiple ML algorithms and reported that the boosted decision tree model showed improved performance compared to the traditional linear regression model. However, among the ML algorithms used in Sampa's study, the model using a neural network exhibited a lower performance than the linear regression model.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…After data augmentation, the vectors need to be regenerated for the new augmented images by updating the parameters. For the rotated images, the values are updated by adding θ with ∆x i and ∆y i , equation (10). To update the vector for parallel-shifting, dx and dy is added to x i and y i , equation (11).…”
Section: Regenerating Sequence Datamentioning
confidence: 99%
“…In addition to ba-PWV, machine learning (ML) is a promising tool in prediction and classification, especially in various applications in a clinical setup. ML approaches have been used in predicting UA level with sociodemographic characteristics, clinical measurements, and dietary information as the inputs [4,13,14]. Performance was measured in terms of area under the curve (AUC), root mean square error (RMSE), sensitivity (Se), and specificity (Sp).…”
Section: Introductionmentioning
confidence: 99%